Menggagas Peradilan Etik Penyelenggara Negara Di Indonesia - Harmoko M. Said (SASI, 2021)
The more complex the problems of state governance are so that corruption, collusion and nepotism are increasingly becoming serious concerns. As for the purpose of this writing is to develop the science of constitutional law in the field of state administration ethics considering the development of an increasingly democratic Indonesian society, demanding an ethical justice system that is effective, efficient, professional, transparent, accountable and reliable for public officials and aims for the rule of law paradigm. law is in line with the rule of ethics paradigm. The type of research used is juridical normative, namely explaining various literatures and / or literature. research results in initiating ethical judiciary for state administrators in Indonesia, due to the increasing number of ethical code enforcement agencies in each branch of power. The Rule of Etich is an instrument that must be implemented for all citizens in the life of the nation and state, in initiating an ethical court in Indonesia it is very urgent. The urgency of establishing an ethical judiciary in Indonesia is due to philosophical factors as reflected in the Pancasila that all five precepts are ethical grounds, juridical factors as regulated in the 1945 Constitution and MPR Decree No.V1 / MPR / 2001, with this juridical foundation, it is clear that the organizers the state is obliged to behave properly. While the sociological factor is the increasing number of ethical code enforcement agencies in each power clump, therefore the consolidation of ethical code enforcement agencies and the establishment of ethical courts is urgent due to the weak adjudication process of the Institute.